(untitled) (Revista de História Regional, 2022)
This text aims to historically analyze the implementation of the rural extension service in Santa Catarina, considering it as part of the diffusion of a political repertoire associated with the so-called theories of modernization. Based on documentation produced in the 1960s, it is intended to highlight the social and cultural implications of political options around the construction of entrepreneurial agricultural practices, highlighting the regional scale as capable of providing the observation of a phenomenon that marks the present time in Brazil.